Safe drinking water: effect of granular activated carbon bed characteristics on iron removal from water (Chemical Engineering Research Bulletin, 2016)
Tuning the characteristics of granular activated carbon bed (GAC-bed) in household water-filters would be a technique to maintain iron at the required-level in drinking water. In the present study the individual effects of the depth of GAC-bed and the size and porosity of GAC particles on the iron removing capacity are investigated experimentally. A spectrophotometer is used to measure iron-content in water. It is observed that iron removing capacity increases monotonically with the increase in bed-depth regardless of the size of GAC particles. It is also observed that the iron removing capacity decreases drastically with the increase in the size of GAC particles for any fixed bed-depth. Finally the porosity of GAC particles is found to affect the iron removing capacity. The higher the GAC porosity the higher is the iron removing capacity over the considered porosity-range. It is believed that the observations of present study would be useful in adjusting GAC-bed characteristics at the time of designing household water-filters to maintain iron at the required-level.Chemical Engineering Research Bulletin 18(2015) 1-5